INFORMATION SECURITY CHALLENGES IN CLOUD COMPUTING: CRITICAL REVIEWING STUDY - Ahmed Abdulgaffar, Shahad (Acta Scientiae et Intellectus, 2024)
The great increase of intellectual production, the diversity of information sources and containers, and the technical revolution, which led in its turn to a large dependence on the Internet, portals and digital information sources, resulted not only in an emerging need to secure websites, computers, software and information in their various forms, but also in the growing importance of what is called the cloud computing service, which is a technical service that has changed the traditional ways of deploying services by organizations or individuals. The paper aimed at shedding light on the challenges facing cloud-computing technology, especially the information security challenge, in order to try to identify the challenges and solutions that contribute in limiting these challenges. In fact, the lack of independent and detailed studies of these challenges that focus on practical solutions was the motive for conducting this paper. It aims at identifying and collecting the intellectual production, specifying the deficiencies, and looking out for future studies issues bearing in mind the importance of information security and its impact on the continuity and development of technology and facilitating the preservation, sharing and extraction of knowledge.